HUBUNGAN KEBIASAAN KONSUMSI ULTRA-PROCESSED FOODS, AKTIVITAS FISIK, DAN DURASI TIDUR DENGAN STATUS GIZI LEBIH PADA REMAJA DI SMPN 1 TAMBUN SELATAN - Dyah Ayuningtyas (2023)
Overnutrition in adolescents still has a high prevalence and continues to grow every year. This trend increased by 5.2% in adolescents aged 13-15 years and the prevalence reached 20.7% in Bekasi Regency. This study aims to determine the relationship between ultra-processed foods consumption habits, physical activity, and sleep duration with overnutrition in adolescents at SMPN 1 Tambun Selatan. The method in this study used a cross sectional design and used stratified random sampling technique to draw a sample size of 113 respondents. Anthropometric data were obtained by direct measurement, ultra-processed foods consumption habits using FFQ, physical activity data using PAL questionnaire, and sleep duration data using PSQI questionnaire. Data analysis through the Chi-Square test found no relationship between ultra-processed foods consumption habits (p = 0.270), physical activity (p = 0.306), and sleep duration (p = 0.771) with overnutrition in adolescents at SMPN 1 Tambun Selatan. It is expected that adolescents can implement a healthy diet and lifestyle by limiting the consumption of foods high in sugar, salt, and sodium, increasing physical activity, and sleeping with sufficient duration to prevent an increase in the prevalence of overnutrition.